Species diversity of dragonfly (arthropoda: odonata) and its relationship with air parameters at Sg. Muar, Kuala Pilah / Nur Hasyimah Ramli and Nur Farahah Abdul Manaf - Ramli, Nur Hasyimah; Abdul Manaf, Nur Farahah (Universiti Teknologi MARA, Negeri Sembilan, 2021)
The study of diversity and distribution of dragonfly, and their relationship with air parameters (temperature (°C) and humidity (%)) at Sg. Muar, Kuala Pilah, Negeri Sembilan was carried out on 14 and 15 March 2020. The sampling of dragonfly was done in two parts of Sg. Muar, Kuala Pilah. For each site, the sampling was conducted in the morning (8-9 a.m) and evening (6-7 p.m) with the air temperature and humidity were recorded at the same time using the hygrometer and digital thermometer clock humidity temperature HTC-1. Sample collections are carried out by sweeping the samples using sweep net. The samples were collected, preserved and identified until species level. A total of 231 individuals were recorded with Ischnura elegans from Coenagrionidae family as a dominant species with 145 individuals (63%), while the lowest abundance is Pseudagrionidae sp. of Coenagrionidae family with one individual (0.004%) only. Meanwhile, there is no significant relationship (p<0.05) between air parameters with individual number of dragonflies. As a recommendation, other parameters of air and water should be measured to increase our understanding on its effects towards the survivability of dragonfly. This research gives benefit to society and ecology, where it can be used as guidelines for future research, update the checklist of dragonfly and conservation purpose in Sg. Muar, Kuala Pilah.